1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: A problem with Wald's General Relativity

  1. Jun 24, 2011 #1
    1. The problem statement, all variables and given/known data

    This problem is Problem 5 in Chapter 4. It is that [itex]T_{ab}[/itex] is a symmetric, conserved field ([itex]T_{ab}=T_{ba}, \partial ^aT_{ab}=0[/itex]) in Minkowski spacetime. Show that there is a tensor field [itex]U_{acbd}[/itex] with the symmetries [itex]U_{acbd}=U_{[ac]bd}=U_{ac[bd]}=U_{bdac}[/itex] such that [itex]T_{ab}=\partial^c\partial^dT_{acbd}[/itex].

    Wald gave a hint: For any vector field [itex]v^a[/itex] in Minkowski spacetime satisfying [itex]\partial_av^a=0[/itex] there is a tensor field [itex]s^{ab}=-s^{ba}[/itex] such that [itex]v^a=\partial_bs^{ab}[/itex]. Use this fact to show that [itex]T_{ab}=\partial^cW_{cab}[/itex] with [itex]W_{cab}=W_{[ca]b}[/itex]. The use the fact that [itex]\partial^cW_{c[ab]}=0[/itex] to derive the desired result.

    3. The attempt at a solution

    Based on his hint, I got a solution [itex]T_{ab}=\partial^c\partial^dU_{acbd}[/itex]. Like [itex]s^{ab}=-s^{ba}[/itex], I required that [itex]U_{acbd}=-U_{adbc}[/itex], but this condition would lead to the result [itex]T_{ab}=0[/itex]!!!!

    So what is wrong with my solution? I need your help, Thank you!
  2. jcsd
  3. Jun 24, 2011 #2
    Could you show your calculation in a bit more detail, please? Otherwise it is difficult seeing where you went wrong, as I haven't done the calculation.
  4. Jun 24, 2011 #3
    Thanks for your reply! I will show my calculation.

    To derive [itex]T_{ab}=\partial^cW_{cab}[/itex], just consider the components [itex]{T^a}_{\mu}={T^a}_b(\partial_\mu)^b[/itex] which is a vector satisfying [itex]\partial_a{T^a}_\mu=0[/itex]. So according to the hint, there exits a tensor [itex]{W^{ca}}_\mu[/itex] such that [itex]{T^a}_\mu=\partial_c{W^{ca}}_\mu[/itex]. Therefore, [itex]T_{ab}=\partial^cW_{cab}[/itex]. Of course, [itex]{W^{ca}}_\mu={W^{[ca]}}_\mu[/itex].

    Then, to get the final result, we just use this fact [itex]\partial^cW_{c[ab]}=0[/itex] or [itex]\partial_c{W^c}_{\mu\nu}=0[/itex]. So there is a tensor [itex]{{{U^c}_{\mu \nu}}}^d=-{{U^d}_{\mu \nu}}^c[/itex] with [itex]{W^c}_{\mu \nu}=\partial_d{{U^c}_{\mu \nu}}^d[/itex]. Then, [itex]{W^c}_{ab}=\partial_d{{U^c}_{ab}}^d[/itex].

    In the end, [itex]T_{ab}=\partial^cW_{cab}=\partial^c\partial^dU_{cabd}=-\partial^c\partial^dU_{acbd}[/itex].

    That's all. The only thing about my final result is that there is an overall minus sign, which is trivial.
  5. Jun 25, 2011 #4
    The original theorem was that for any v^a with d_a v^a = 0, there is an antisymmetric tensor s^{ab} such that v^a = d_b s^{ab} = - d_b s^{ba}. So you should have T^a_μ = ∂_c W^{ac}_μ, which is minus the result you gave. Of course you can always redefine W to be -W, but let's stick with mine for now.

    Evidently. So T^{ab} = ∂_c W^{acb} with W^{acb} = W^{[ac]b}.

    I don't see it that clearly. Let's see, from the symmetry of the energy-momentum tensor we get
    ∂_c W^{cab} = - ∂_c W^{acb} = - ∂_c W^{bca} = ∂_c W^{cba}
    so, yes, check.

    Yes. So, T^{ab} = ∂_c W^{acb} = ∂_c ∂_d U^{acbd}, and we found your minus sign. For the symmetries, we know that W^{acb} = - W^{cab} = - W^{cba}. Let's check the symmetries of U. First, it is antisymmetric in the first and last index from the definition, so U^{acbd} = - U^{dcba}. From the W symmetries it gets U^{acbd} = - U^{cabd} = - U^{cbad}, and that should be all. So we still need that U^{acdb} = - U^{acbd} and U^{acbd} = U^{bdac} according to Wald, let's see if we can achieve this.
    U^{bdac} = U^{badc} = - U^{cadb} = U^{acdb}
    No! Doesn't work. I think you should set W^c_{μν} = ∂_d U^{cd}_{μν} and not ∂_d U^c_{μν}^d , because you don't get the required symmetries otherwise. With that choice, T^{ab} also shouldn't vanish anymore :)
  6. Jun 25, 2011 #5
    Thanks for your reply! But you see, we agree that [itex]{U^{cd}}_{\mu \nu}[/itex](your notation) or [itex]{{U^c}_{\mu \nu}}^d[/itex] (my notation) should be antisymmetric in indices c and d, then [itex]T_{ab}=\partial^c \partial^d U_{cdab}[/itex] or [itex]T_{ab}=\partial^c \partial^dU_{cabd}[/itex] is zero since [itex]\partial^c\partial^d=\partial^d\partial^c[/itex]. Is that right?
  7. Jun 27, 2011 #6
    Yes, with your notation T^{ab} comes out zero. With the notation I proposed also, I see it now. But note that in the original problem the derivatives should act on the first and third index of U, so that T doesn't vanish. So you should take W^c_{μν} = ∂_d U^c_μ^d_ν, sorry for the confusion before.
  8. Jun 29, 2011 #7
    Sorry. I was busy those days. Hmmm, I do not think we can put the indices in arbitrary position. And even if you take W^c_{μν} = ∂_d U^c_μ^d_ν, we still have to assume that U_{cadb}=-U_{dacb}, that is, antisymmetric in the first and the third indices. So still, we get a vanishing T_{ab}.
  9. Jun 30, 2011 #8
    But yes, you can, since μ and ν are not Lorentz indices, and the first theorem (that v^a = ∂_b s^{ab}) only makes a statement about Lorentz indices.

    U is antisymmetric in the first and second index, and separately in the third and fourth, but not in the first and third. So only in that case T^{ab} is not zero.
  10. Jul 1, 2011 #9
    Well, I really cannot agree with you, but can you introduce some material on tensor, especially on indices? I will appreciate it!
  11. Dec 12, 2013 #10
    Then, to get the final result, we just use this fact [itex]\partial^cW_{c[ab]}=0[/itex] or [itex]\partial_c{W^c}_{\mu\nu}=0[/itex].

    Pretty sure what you said above was wrong, [itex] \partial ^cW_{c[ab]}=0 [/itex] does not imply that [itex]\partial d ^cW_{cab}=0[/itex]. If it did it would mean then the stress energy tensor is zero from the step before.
    Last edited: Dec 12, 2013
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted